Antifungal efficacy of Zanthoxylum oil against Bipolaris sorokiniana (Sacc.) Shoem. - Manandhar, Anshu; Tiwari, R. D. (Ecoprint: An International Journal of Ecology, 2010)
Bipolaris sorokiniana (Sacc.) Shoem. is the most economically important foliar blight pathogen of wheat in all warm zones. Essential oil of Zanthoxylum armatum D.C. was used to determine its efficacy against Bipolaris sorokiniana by calculating the percentage of mycelial growth inhibition. The oil showed 25, 37.8, 42.8, 75, 84.5 and 100 percent inhibition of mycelial growth at 5.0, 10.0, 15.0, 20.0, 30.0 and 40.0 μl ml-1 ppm concentrations of essential oil against the test fungus, respectively. Keywords: Essential oil, fungitoxicity doi: 10.3126/eco.v12i0.3206 Ecoprint: An International Journal of Ecology 12: 91-93, 2005